2006
DOI: 10.1111/j.1462-2920.2006.01181.x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional cattle manure application determines abundance, diversity and activity of methanogenic Archaea in arable European soil

Abstract: CitationTraditional cattle manure application determines abundance, diversity and activity of methanogenic Archaea in arable European soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 44 publications
6
42
0
Order By: Relevance
“…The effect of fertilizer type was smaller than soil type, although archaeal populations were significantly higher in organic fertilizer-added soil than soils with added chemical fertilizers. The effect of organic fertilizer detected in our field corresponded with previous reports using archaeal phospholipid etherlipid (PLEL) concentrations (8) and 16S rRNA gene copy numbers (42) as indicators of archaeal biomass.…”
Section: Population Of Field Soil Archaeasupporting
confidence: 72%
See 2 more Smart Citations
“…The effect of fertilizer type was smaller than soil type, although archaeal populations were significantly higher in organic fertilizer-added soil than soils with added chemical fertilizers. The effect of organic fertilizer detected in our field corresponded with previous reports using archaeal phospholipid etherlipid (PLEL) concentrations (8) and 16S rRNA gene copy numbers (42) as indicators of archaeal biomass.…”
Section: Population Of Field Soil Archaeasupporting
confidence: 72%
“…In Andosol, organic fertilizer decreased archaeal diversity, diminishing many minor bands and increasing the intensity of some bands. Other reports have also shown that long-term application of fertilizers affected archaeal communities (8,24). Nicol et al (25) reported that grassland management resulted in a reproducible shift in archaeal DGGE profiles and Gettinger et al (8) showed that molecular archaeal diversity was lower in highest fertilized treatments by cattle manure than in normal mineral fertilized treatments.…”
Section: Diversity Of Field Soil Archaeamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous surveys of soil archaea have typically examined a limited number of samples or sites, often focusing on only a single category of soils, such as agricultural soils (Buckley et al, 1998;Furlong et al, 2002;Gattinger et al, 2007) or soils from extreme environments including deserts and recently deglaciated sites Pointing et al, 2009;Soule et al, 2009). The most comprehensive survey of archaeal populations to date (Auguet et al, 2009) provided valuable insight into broad-scale ecological patterns exhibited by the archaeal domain in general.…”
Section: Introductionmentioning
confidence: 99%
“…First, we considered the number of animals (poultry, pigs and cattle) living on the catchment area and the expected amount of waste material produced by these animals (Biomasse Normandie, 2002). Secondly, a literature survey on concentrations of water extractable organic carbon (WEOC) of various animal wastes, including cattle manure (CM), pig manure (PM) and poultry litter (PL), was conducted (Bernal et al, 1998;Huang et al, 2004;Zmora-Nahum et al, 2005;Angers et al, 2006;Aira et al, 2007;Gattinger et al, 2007;Guo et al, 2009; Table 3). Some discrepancies were found between studies, however, an average WEOC concentration of 12 mg g À1 for all manure types was retained as it is in accordance with most of the reports.…”
Section: Sampling Datementioning
confidence: 99%